(untitled) (Journal of Biomedical Investigation, 2015)
Nigeria has a high maternal mortality that is disproportionate to its population relative to that of the world. This review examines maternal mortality in Nigeria with respect to the magnitude of the problem, its causes, together with the pattern of maternal health services and their influence on maternal mortality. Among direct medical causes of maternal mortality in Nigeria include hemorrhage (23 %), sepsis (17 %), malaria, anemia, abortion, hypertensive disorders/eclampsia, obstructed labour (11 % each) and others (5 %). Non-medical factors which include sociocultural, economic, and legal factors, reproductive health factors, health services and health system factors, and delay in access to emergency obstetrics care; all impede availability and access to maternal health services, thereby promoting maternal mortality. The knowledge of these factors will redirect the thought and actions of stakeholders in maternal health towards a better focused planning and implementation of maternal mortality reduction in Nigeria.